Isolating Low Concentration of Tritium in Potable Water Using Simple Designed and Fabricated Process. (3rd April 2017) - Ozemoyah, Peter; Robinson, John
Abstract: Tritium in everyday water (potable water) is frequently of a level that is too low for measurement with conventional instrumentation that is affordable by small laboratories. Scintillation counters that can measure in fractions of Becquerels per litre are usually out of the reach of most laboratories, especially in developing countries. By concentrating the tritium by a known amount, it can reach measurable levels that can be converted back to the original concentration. Affordability of the concentrating process is vital in the overall process. A simple concentrating process based on purification and electrolysis was designed and fabricated. The tritium isotope enrichment level, the volumetric reduction and the time frame required for the enrichment were determined using the simple designed and fabricated process, and an easily affordable scintillation counter. The simple designed and fabricated system effectively concentrated the tritium in the sampled water several times the initial value. The enrichment resulted in the output product being measurable in a non-expensive scintillation counter.